2020
DOI: 10.5354/0719-0581.2020.55711
|View full text |Cite
|
Sign up to set email alerts
|

Discriminación, aculturación y bienestar psicológico en inmigrantes latinoamericanos en Chile

Abstract: La literatura acerca del bienestar psicológico de los inmigrantes ha identificado la discriminación percibida como una fuente importante de estrés que puede mermar su ajuste psicológico en el país de recepción. Asimismo, existe evidencia respecto del impacto de la aculturación en el funcionamiento psicológico positivo de esta población. Este trabajo indaga en las relaciones entre la discriminación, las orientaciones de aculturación y el bienestar psicológico de 152 inmigrantes latinoamericanos que residen en C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
1
5
0
1
Order By: Relevance
“…Besides, students reported high levels of management in cultural diversity scenarios at school, feeling capable to process information from other cultures, mixing satisfactorily with other cultures, and understanding other ways of life. These results coincide with those informed by Rania et al (2012) and also with previous findings from studies conducted with immigrants and natives in Chile ( Mera-Lemp et al, 2020a , b ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, students reported high levels of management in cultural diversity scenarios at school, feeling capable to process information from other cultures, mixing satisfactorily with other cultures, and understanding other ways of life. These results coincide with those informed by Rania et al (2012) and also with previous findings from studies conducted with immigrants and natives in Chile ( Mera-Lemp et al, 2020a , b ).…”
Section: Discussionsupporting
confidence: 93%
“…Important aspects of school life are grades and other accomplishments ( Casas et al, 2013 ) that are related to self-efficacy. In the context of these participants, the sense of successfully managing in a multicultural classroom can give them this feeling of competence ( Vecchio et al, 2007 ; Mera-Lemp et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Colombian population in Chile has reported multiple experiences of discrimination, either by the country of origin, linked to drug trafficking, drugs, and sex trade in the case of women, or based on the color of the skin (many migrants are African descendants) [ 69 , 70 , 71 ]. Previous studies in Chile reported how discrimination has negatively affected both the mental health and the well-being of this population [ 72 , 73 ], in addition to other factors that also affect well-being [ 74 , 75 , 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…This migration has resulted in situations of discrimination, either by the country of origin, linked to drug trafficking, drugs, and sex trade in the case of women, or by the color of the skin (Pavez, 2016;Tijoux, 2016;Gissi et al, 2019). Studies conducted in Chile show how discrimination has negatively affected both the mental health and the wellbeing of this population (Urzúa et al, 2018(Urzúa et al, , 2019bMera-Lemp et al, 2020a), in addition to other factors that also affect wellbeing (Silva et al, 2016;Urzúa et al, 2019aUrzúa et al, , 2020bMera-Lemp et al, 2020b). A qualitative perspective about the effects of migration and racism on the Colombian population in Chile can be reviewed in Gii-Barbieri and Ghio-Suárez 2017and Gii et al (2019).…”
Section: Introductionmentioning
confidence: 99%